PEMANFAATAN PENAMPUNGAN AIR HUJAN UNTUK PEMENUHAN KEBUTUHAN AIR DOMESTIK DI DESA SONGBLEDEG KECAMATAN PARANGGUPITO KABUPATEN WONOGIRI TAHUN 2021 - Ibet Nurbaiti; Setya Nugraha; Gentur Adi Tjahjono (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2023)
Karst areas are known as areas that often experience drought problems. the south wonogiri area often experiences a shortage of clean water, because there is no source of clean water that can be utilized. Songbledeg Village is one of the villages in Paranggupito sub-district that utilizes rainwater reservoirs as the main water source to meet domestic water needs. The purposes of this research were: (1) Domestic water needs of residents in Songbledeg Village Paranggupito District Wonogiri Regency in 2021; (2) effectiveness of rainwater storage to meet domestic water needs in Songbledeg Village Paranggupito District Wonogiri Regency in 2021; (3) effectiveness rainfall to support rainwater storage in Songbledeg Village Paranggupito District Wonogiri Regency in 2021. This study uses a quantitative descriptive method with a spatial approach. The result of this study were: (1) the domestic water demand in Songbledeg Village is 251.900 liters/day with a total population of 2.519 people spread across 13 hamlets namely Klepu Hamlet, Mloko Hamlet, Lomujing Hamlet, Sumberjo Hamlet, Bulu Hamlet, Jamburejo Hamlet, Weru Hamlet, Ngandongrejo Hamlet, Rejosari Hamlet, Songbledeg Hamlet, Janglot Hamlet, Gondangsari Hamlet, and Tlogorejo Hamlet; (2) the effectiveness of rainwater storage in Songbledeg Village is the highest at 22.8 % with a storage capacity of 30.000 liters and then lowest is 2.4 % with a storage capacity of 6.000 liters; (3) the average rainfall in Songbledeg Village which is 1501.83 mm/year cannot support the utilization of rainwater reservoirs in Songbledeg Village.